2018
DOI: 10.1002/jcb.27449
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional analysis reveals altered chromatin interaction by enhancer inhibitors harbors TCF7L2‐regulated cancer gene signature

Abstract: Distal regulatory elements influence the activity of gene promoters through chromatin looping. Chromosome conformation capture (3C) methods permit identification of chromatin contacts across different regions of the genome. However, due to limitations in the resolution of these methods, the detection of functional chromatin interactions remains a challenge. In the current study, we employ an integrated approach to define and characterize the functional chromatin contacts of human pancreatic cancer cells. We ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…Previous work had developed 3D chromatin structure of pancreatic cancer, but they focused on structural variants detection [ 33 ] by Hi-C and TAD alterations [ 34 , 35 ]. Here, we reported sub-5-kb resolution Hi-C maps to identify contact domain and loop alterations during pancreatic cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work had developed 3D chromatin structure of pancreatic cancer, but they focused on structural variants detection [ 33 ] by Hi-C and TAD alterations [ 34 , 35 ]. Here, we reported sub-5-kb resolution Hi-C maps to identify contact domain and loop alterations during pancreatic cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…We, therefore, examined the relationship between higher-order chromatin organization and broad epigenetic domains in PANC1 cells. Genome-wide chromatin contacts were determined by analyzing tethered-chromatin conformation capture (TCC) data in PANC1 [43]. Chromatin contacts were partitioned into topologically associated domains (TADs) and TAD boundary regions using a resolution of 40 kb ( Figure 5A and Figure S6).…”
Section: Hat Inhibitor Treatment Targets Broad Domains That Are Enricmentioning
confidence: 99%
“…However the specific role of TCF7L2 in the development of BE is not fully understood. Previous studies have shown that TCG7L2 is closely associated with the development, progression and distant metastasis of various cancers such as pancreatic cancer 41 . The overexpressed TCF7L2 was associated with poor overall survival in patients with glioma 42 .…”
Section: Discussionmentioning
confidence: 98%